A review of uncertainty in environmental risk: characterising potential natures, locations and levels - Skinner, Daniel J. C.; Rocks, Sophie A.; Pollard, Simon J. T. (Taylor & Francis, 2013)
Uncertainties, whether due to randomness or human or system errors, are inherent within any decision process. In order to improve the clarity and robustness of risk estimates and risk characterisations, environmental risk assessments (ERAs) should explicitly consider uncertainty. Typologies of uncertainty can help practitioners to understand and identify potential types of uncertainty within ERAs, but these tools are yet to be reviewed in earnest. Here, we have systematically reviewed 30 distinct typologies and the uncertainties they communicate and demonstrate that they: (1) use terminology that is often contradictory; (2) differ in the frequencies and dimensions of uncertainties that they include; (3) do not uniformly use systematic and robust methods to source information; and (4) cannot be applied, on an individual basis, to the domain of ERA. On the basis of these observations, we created a summary typology – consisting of seven locations (areas of occurrence) of uncertainty across five distinct levels (magnitude of uncertainty) – specifically for use with ERAs. This work highlights the potential for confusion, given the many versions of uncertainty typologies which exist for closely related risk domains and, through the summary typology, provides environmental risk analysts with information to form a solid foundation for uncertainty analysis (based on improved understanding) to identify uncertainties within an ERA.
Keywords: uncertainty; typology; environmental; risk; assessment